Updated Evidence of Association Between Periodontal Disease and Incident Erectile Dysfunction. Issue 1 (1st January 2019) - Zhou, X.; Cao, F.; Lin, Z.; Wu, D.
Abstract: Introduction: The relationship between periodontal disease (PD) and erectile dysfunction (ED) is still conflicting. Aim: To investigate whether a link between PD and ED exists, and if so, the degree to which it is significant. Methods: The search strategy included using electronic databases and hand searching works published up to June 2018. MEDLINE via PubMed, EMBASE, Proceedings Web of Science, and Current Contents Connect were searched by 2 independent reviewers. Case-control, cohort, or cross-sectional studies including patients with measures of periodontitis and ED were included in the analysis. Quality assessments and sensitivity analysis of selected studies were performed. Main Outcome Measure: The strength of the association between PD and the prevalence of ED was evaluated. Results: 5 case-control studies with 213, 076 participants met the eligibility criteria and were included in the meta-analysis. Patients with PD were 2.85-fold more likely to be diagnosed with ED (OR = 2.85, 95% CI = [1.83, 4.46]). Asian men were reported to be 3.07 times more likely to be at greater risk for the prevalence of ED. Moreover, studies with high quality and case-control design showed 2 times higher risk for ED in PD (OR = 2.44, 95% CI = [1.44, 4.14]). However, the present evidence was not robust enough owing to the high heterogeneity and instability in sensitivity analysis. Clinical Implications: Patients with PD may have increased risk of ED, suggesting that dental hygiene should be of concern to clinicians when managing patients with ED. Strength & Limitations: This article includes a large literature search to confirm the evidence that PD increases the occurrence of ED. However, there are several confounders, such as age and the type of ED, that failed to be adjusted and that generate bias and affect the correlation between the incidence of ED and PD. Conclusion: This system review and meta-analysis strengthens the evidence that PD might have important clinical implications for risk stratification of ED.